2002
DOI: 10.1111/j.1471-0528.2002.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of outpatient endometrial biopsy in the diagnosis of endometrial cancer: a systematic quantitative review

Abstract: Outpatient endometrial biopsy has a high overall accuracy in diagnosing endometrial cancer when an adequate specimen is obtained. A positive test result is more accurate for ruling in disease than a negative test result is for ruling it out. Therefore, in cases of abnormal uterine bleeding where symptoms persist despite negative biopsy, further evaluation will be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(138 citation statements)
references
References 59 publications
4
131
1
2
Order By: Relevance
“…5,34,35 If the material is sparse or otherwise unfit for histopathological diagnosis, a formal curettage procedure with specimens collected from the cervix and uterine body separately (fractionated curettage) is performed. By bimanual palpation, size of the uterus is estimated and a rough assessment of the uterine mobility performed as part of the evaluation of operability.…”
Section: Biopsy Cytology and Curettagementioning
confidence: 99%
“…5,34,35 If the material is sparse or otherwise unfit for histopathological diagnosis, a formal curettage procedure with specimens collected from the cervix and uterine body separately (fractionated curettage) is performed. By bimanual palpation, size of the uterus is estimated and a rough assessment of the uterine mobility performed as part of the evaluation of operability.…”
Section: Biopsy Cytology and Curettagementioning
confidence: 99%
“…Clark et al [18] found that an endometrial biopsy result showing cancer was more accurate at ruling in disease than a negative test result was at ruling it out, with a post test probability of 81.7% for a positive result and 0.9% for a negative result. 18 Bansal et al reported that the overall ability of preoperative endometrial sampling to detect a malignancy was significantly lower for non-endometrioid histologies with 75% accuracy for uterine papillary serous and clear cell carcinomas, 59% for carcinosarcoma, and 52% for other sarcomas [19]. Sany et al [20] described a correlation between underlying histology and the ability to make an accurate diagnosis based on preoperative endometrial sampling (endometroid carcinoma 78%, nonendometrioid carcinoma 67%, carcinosarcoma 90%, and sarcoma 40%) [20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the diagnosis is more likely to be missed if the cancer is localized to an endometrial polyp or occupies less than 50% of the endometrium [17]. Clark et al [18] found that an endometrial biopsy result showing cancer was more accurate at ruling in disease than a negative test result was at ruling it out, with a post test probability of 81.7% for a positive result and 0.9% for a negative result. 18 Bansal et al reported that the overall ability of preoperative endometrial sampling to detect a malignancy was significantly lower for non-endometrioid histologies with 75% accuracy for uterine papillary serous and clear cell carcinomas, 59% for carcinosarcoma, and 52% for other sarcomas [19].…”
Section: Discussionmentioning
confidence: 99%
“…It also should provide adequate and high-quality tissue samples for histopathological diagnosis without major complications. 12 Previously, dilatation and curettage (D&C) was the most commonly used method for endometrial sampling. Nowadays, because D&C is an expensive and invasive method and requires general anesthesia and hospitalization, it has been replaced by aspiration techniques.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%